2023
DOI: 10.3390/v15051045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mimicry of the Viral Spike in the SARS-CoV-2 Vaccine Possibly Triggers Transient Dysregulation of ACE2, Leading to Vascular and Coagulation Dysfunction Similar to SARS-CoV-2 Infection

Abstract: The benefits of SARS-CoV-2 spike mRNA vaccines are well known, including a significant decline in COVID-19 morbidity and a decrease in the mortality rate of SARS-CoV-2 infected persons. However, pharmacovigilance studies have revealed the existence of rare cases of cardiovascular complications after mass vaccination using such formulations. Cases of high blood pressure have also been reported but were rarely documented under perfectly controlled medical supervision. The press release of these warning signals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 114 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…On the one hand, the benefits of SARS-CoV-2 spike mRNA vaccines are well known, including a significant decline in COVID-19 morbidity and a decrease in the mortality rate of SARS-CoV-2 infected persons. On the other hand, pharmacovigilance studies have revealed the existence of rare cases of cardiovascular complications after mass vaccination using such formulations as what we consider how Acute Vascular Distress Syndrome [126], which coincides with other data. The effect of SARS-CoV-2 Infection and BNT162b2 Vaccination on the mRNA Expression of Genes Associated with Angiogenesis contributes to the development of adverse cardiovascular effects [127].…”
Section: Multi-organ Supportive Therapy (Most) Extracorporeal Life Su...supporting
confidence: 89%
“…On the one hand, the benefits of SARS-CoV-2 spike mRNA vaccines are well known, including a significant decline in COVID-19 morbidity and a decrease in the mortality rate of SARS-CoV-2 infected persons. On the other hand, pharmacovigilance studies have revealed the existence of rare cases of cardiovascular complications after mass vaccination using such formulations as what we consider how Acute Vascular Distress Syndrome [126], which coincides with other data. The effect of SARS-CoV-2 Infection and BNT162b2 Vaccination on the mRNA Expression of Genes Associated with Angiogenesis contributes to the development of adverse cardiovascular effects [127].…”
Section: Multi-organ Supportive Therapy (Most) Extracorporeal Life Su...supporting
confidence: 89%
“…For mRNA-based vaccines (e.g., mRNA-1273 SARS-CoV-2 vaccine [Moderna] and BNT162b2 mRNA Covid-19 vaccine [Pfizer/BioNTech]), potential biological mechanisms for an increased risk of immune-mediated diseases include mRNA’s intrinsic immunostimulatory properties. The vaccine’s end-protein (spike protein), by mimicking the behavior of the virus, can bind to ACE2, disrupt the body’s normal RAS, and cause endothelial injury 9 , 27 , 44 , 45 . Endothelial damage can trigger the development of anti-endothelial antibodies (e.g., anti-AT1R antibody) which can attack multiple organs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial damage can trigger the development of anti-endothelial antibodies (e.g., anti-AT1R antibody) which can attack multiple organs 46 . If there is a dysregulated, prolonged innate immune response, these changes may cause systemic inflammation and contribute to the development of autoimmune reactions and multiorgan injuries in some individuals after COVID-19 vaccination 9 , 27 , 44 , 45 . The role of anti-AT1R antibody was investigated in our case based on the resembling features of its involvement in both COVID-19-related multiorgan injury and AMR in solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore refer readers to these papers [ 26 , 175 - 181 ]. The mechanisms of molecular mimicry, antigen cross-reactivity, pathogenic priming, viral reactivation, immune exhaustion, and other factors related to immune dysfunction all reinforce the biological plausibility for vaccine-induced pathogenesis of malignant and autoimmune diseases [ 26 , 182 - 185 ]. Both SARS-CoV-2 and the mRNA vaccines can trigger immune dysfunction along with a host of pathophysiological effects, including chronic inflammation, thrombogenesis, prion-related dysregulation, and endotheliitis-related tissue damage [ 180 ].…”
Section: Reviewmentioning
confidence: 99%